Assess The Socioeconomic Burden of Critically Ill Patients, Agra, Uttarpradesh: A Descriptive Study - Kalita, Himadri; Nisha, Sumbul; Reddy, Deepa Ganesh; R, Sathyasri.; Srivastava, Jyoti; P. F, Regina. (Journal of Neonatal Surgery, 2025)
Background: The cost of critical illness treatment is generally recognized as expensive and increasing in India. Critical illness of the individual will affect the socioeconomic status of the individual and the family. The direct and indirect costs of intensive care and its impact on the socioeconomic status of critically ill patients and their families need to be estimated. Objective: To assess the socioeconomic burden of critically ill patients. Methods: The study was conducted in selected hospitals at Uttar Pradesh by two data collectors and selected hospital.60 critically ill patient’s relatives were selected and convenience sampling technique used to select samples. The questionnaire were checked for completeness, cleaned manually and entered in to Epi- Data version 4.2. Then the data was transferred in to SPSS version 21.0 for further analysis. Descriptive statistics were carried out. Finally checked association between dependent and independent variables. Results: revealed that 31 (52%) critically ill patients relatives had poor socioeconomic, 24 (40%) had average socioeconomic, and 5(8%) had well socioeconomic. There was a significant association between socioeconomic status of critically ill patient and their demographic variables such as monthly income of patients. p<0.05 level. There was no association between the demographical variables such as age, gender, resident area, occupational status, socioeconomic status and educational status at p<0.05 level.. Conclusion: Critical care hospitalization of patients increases the socioeconomic burden on the whole family, especially in lower-middle-income countries like India. It soberly affects younger age group patients with low socioeconomic status and families depending on the patient's income during their man days.